Coachability: A Longitudinal Curriculum to Promote Medical Students' Growth Mindset, Feedback Utilization, and Resilience - Gabriella Tison-Brandon; Mary Dickerson; Laryn Sapetti; Raquel Johnson; Anna T. Cianciolo (Association of American Medical Colleges, 2024)
Introduction The concept of medical student coachability, adapted from athletics and business management, offers a framework for characterizing students' roles as clinical learners. We defined coachability as effectively seeking, receiving, and using feedback-even negative feedback-to change behavior and reach learning goals. To facilitate success in our clinical clerkships, we sought to empower preclerkship students' capacity to be coached. Methods Our curriculum comprised two large-group presentations and three small-group seminars totaling approximately 5 hours, distributed over 2 years: a year 1 orientation, a year 2 refresher, and a longitudinal year 2 seminar series. Medical students designed and first implemented the curriculum under faculty supervision in academic year (AY) 2015-2016 and have continuously managed and run it since. The AY 2022-2023 curriculum management team evaluated the curriculum cross-sectionally via student survey and focus groups. Results Approximately 575 students have completed the curriculum since 2015. Immediately following curriculum delivery, AY 2022-2023 year 2 students (response rate: 70%-97%) rated it a valuable educational experience and described plans to implement the lessons learned in their clerkship. Focus group participants (eight clerkship students who participated in the coachability curriculum in AY 2021-2022) reported using coachability strategies to positive effect for their clinical learning and well-being. Discussion Our curriculum's flexible, modular format facilitates adoption by others. Future development could expand coachability offerings across the continuum of medical school. However, the curriculum should remain led by students passionate about medical education and willing to try new things to continuously adapt content and instructional strategies.